PENGEMBANGAN BANK SOAL MATA KULIAH PSIKOLOGI PERKEMBANGAN - Anna Armeini Rangkuti (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2011)
Valid and reliable test is an essential instrument to measure the student’s learning achievement. Standardized test available at the time it is required will make the instructional process more effective and efficient. This study aims at building a test bank with standardized tests for Development Psychology Course as one of Basic Courses for Education that has to be taken by all students of education. The test items were developed by employing the method which could expose psychometric property or psychomotoric characteristics of each item. For this purpose 95 test items were tried out to 224 students of State University of Jakarta. From the whole number of test items, 46 were analyzed by using Rasch Model (Item Response Theory) and the remaining 49 were analyzed with Classical Test Theory. The study resulted in 29 valid test items from Rasch Model and 42 valid test items from Classical Test Theory. The valid test items can be put into the test bank and ready for use.